ANALISIS PELAKSANAAN IDENTIFIKASI PASIEN DALAM RANGKA KESELAMATAN PASIEN DI UNIT RAWAT INAP RUMAH SAKIT UMUM DAERAH KOTA BEKASI - Guesthi Lunes Mutiara Cintha; Antono Suryoputro; Sutopo Patria Jati (Jurnal Kesehatan Masyarakat (Undip), 2016)
The accuracy of patient identification is the beginning of the security services at the Hospital.Hospitals must have a system that can manage security for patients. Errors due to misidentification often become the cause of problems in almost all aspects or stages of diagnosis and treatmentso that the required accuracy of identification.  This research aims to investigate theimplementation of the identification unit Inpatient Hospital Bekasi City using systems theory.This research uses qualitative descriptive method and using the interview guidelines and observation sheet as an instrument.Interviews were conducted with nurses, the head of the room and the staff Bekasi City Hospital patient safety.The results showed that the implementation of the identification of patients at City Hospital inpatient units Bekasi already running but is not yet fully correspond as stipulated in the PMK 1691/Menkes/Per/VII/2011.This is because the human resources are inadequate, the information in identity bracelet isn’t fullyinformatif, lack of training given to nurses, adherence nurses on SOP are still lacking, no progressed in reporting system, supervision is not optimal yet still a constraint in the implementation makingthe implementation becomes not optimal.